Relationship Between Arm Muscle Strength and Eye-Hand Coordination with Underhand Passing Ability in Students - Hikmad Hakim; Suriah Hanafi; Andi Ridwan; Awaluddin Awaluddin (UNIVERSITAS NEGERI MAKASSAR, 2024)
This study aims to determine the relationship between arm muscle strength and eye-hand coordination with underarm passing ability in students. This study is a descriptive study with independent variables consisting of arm muscle strength and eye-hand coordination, and the dependent variable is underarm passing. The population in this study were male students of SMA Negeri 8 Bone class XI with a sample size of 20 people. The instruments in this study used arm muscle strength tests, hand-eye coordination tests, and volleyball underarm passing tests. The results of data analysis showed that there was a significant relationship between arm muscle strength and eye-hand coordination with underarm passing ability in students as evidenced by the observation correlation coefficient (Ro) value of 0.012 with a probability level (0.000) <α: 0.05